Melatonin alters the secondary metabolite profile of grape berry skin by promoting VvMYB14-mediated ethylene biosynthesis - Ma, Wanyun (Hortic Res, 2021)
The interplay between melatonin and ethylene in the regulation of fruit metabolism and the underlying molecular mechanism of this interplay remain largely unclear. Here, widely targeted metabolomics analysis revealed a total of 464 metabolites present in berry skin. Among them, 27 significantly differentially accumulated metabolites (DAMs) were produced in response to melatonin treatment in the presence or absence of 1-MCP. Most of the DAMs were secondary metabolites, including flavonoids, phenolic acids, stilbenes, and flavonols. Additionally, the accumulation of 25 DAMs was regulated by melatonin via ethylene. RNA-seq analysis indicated that melatonin primarily regulated the pathways of plant hormone signal transduction and secondary metabolite biosynthesis via ethylene. Gene-metabolite association analysis showed that melatonin regulated the expression of the VvSTS1, VvF3H, VvLAR2, and VvDFR genes, suggesting that these genes may play key roles in regulating secondary metabolites in the skin; additionally, VvMYB14 and VvACS1 were suggested to be involved in the regulation of secondary metabolites. Further experiments revealed that melatonin induced the expression of VvMYB14 and that VvMYB14 increased ethylene production by transcriptionally activating VvACS1, thereby affecting the accumulation of secondary metabolites. Collectively, melatonin promotes ethylene biosynthesis and alters secondary metabolite accumulation through the regulation of VvACS1 by VvMYB14.